FORMAÇÃO CONTINUADA DE PROFESSORES QUANTO ÀS TEMÁTICAS MUNDO DO TRABALHO E PERSPECTIVA DE VIDA - Aléx Gomes da Silva; Raquel Rosan Christino Gitahy (Universidade do Oeste Paulista, 2015)
This paper was carried out to analyze the contributions made by the Educational Program to Provide Care for Youth (Peas Juventude) to further teachers' continued education, the broaching both by teachers and youth of issues related to the World of Labor and Perspective on Life, discussing entrepreneurship, interpersonal relations, skills and competence, dreams and wishes, personal and professional growth. It is a continued education in work, with direct and positive interference in their school environment.